The book swap - Bickers, Tessa (Graydon House, 2024)
Still grieving the death of her best friend, Erin knows she needs to start living - but has no idea how. Then she loses her favourite book, a heavily annotated and containing her friend's final words to her. When James finds Erin's note-filled book in his local community library, it sparks a life-changing conversation. He writes his own message back, and soon they are locked in an anonymous book exchange, with no idea who the other person in the margins might be. But Erin and James have a shared history that neither of them realise. How will Erin react when she discovers the other writer isn't a stranger at all - but the person she once swore she'd never forgive?